Efficacy of the Japanese herbal medicine rikkunshito in infants with gastroesophageal reflux disease. Issue 4 (25th March 2015) - Otake, Kohei; Uchida, Keiichi; Mori, Koichiro; Ide, Shozo; Koike, Yuhki; Takamura, Mitsuyuki; Inoue, Mikihiro; Kusunoki, Masato
Abstract Background Gastroesophageal reflux disease (GERD) in infants is among the most common reason for physician consultation worldwide. A traditional Japanese medicine, rikkunshito (RKT), is effective for GERD in adult and pediatric patients. The aim of this study was to evaluate the efficacy and safety of RKT in infants with GERD. Methods Fifty‐four infants were referred to between July 2004 and December 2012 for evaluation and treatment of GERD. All infants had failure to thrive. We excluded nine patients with cow's milk protein allergy, neurological impairment or surgical indications. We retrospectively reviewed the clinical records of 45 infants with GERD. Twenty‐nine infants were treated with RKT (TJ‐43; 0.3 g/kg/day; RKT group), and 16 infants were treated with mosapride citrate at 0.5 mg/kg/day (mosapride group). The primary endpoint was RKT‐induced relief of clinical symptoms and bodyweight gain in infants with GERD. Results After 3 months of treatment, the frequency of vomiting per day was significantly lower in the RKT group than in the mosapride group (P = 0.0146) and the weight Z‐score was significantly higher in the RKT group than in the mosapride group (RKT group, −2.5 ± 1.5 vs mosapride group, −5.0 ± 2.0; P = 0.0386). No adverse effects were noted in either group. Conclusions RKT may be safe and effective for relief of GER symptoms and for bodyweight gain in infants with GERD.